Implicit Res Judicata in Peruvian Law: Comparative Analysis and Recommendations for its Implementation - Horna León, Percy Hardy (2025)
This paper discusses the institution of res judicata in Peruvian procedural law, emphasizing its role in ensuring stability and legal certainty. It examines how Peruvian law currently upholds the “triple identity” theory (parties, subject matter, and cause of action) to determine res judicata, along with the limitations that such a conception imposes on conflict resolution. For this reason, the paper proposes the implementation of implicit res judicata, based on comparative experiences in Spanish and Anglo-Saxon law, where the scope of res judicata is extended to issues that were not debated but could have been raised in the initial proceedings. This approach allows for a much more efficient judicial system by reducing the number of cases concerning similar matters.